Current stocks of 137Cs and 90Sr in forest litters of oak forests in the Chernobyl nuclear power plant near zone - Garbaruk, Dmitriy; Uglyanets, Anatoliy (Journal of the Belarusian State University. Ecology, 2025)
The results of the study of 137Cs and 90Sr content in forest litter of oak forests of the near zone of the Chernobyl nuclear power plant within the boundaries of the protected area of the Polessky State Radiation and Ecological Reserve of Belarus are presented. In 2021, before the beginning of leaf fall, the total 137Cs stock in the litter of oak forests in this area was estimated at (1.65–2.02)×1012 Bq, 90Sr – at (0.51–0.80)×1012 Bq. The specific weight of 137Cs accumulated in them was 40.5–45.1 % of the total radionuclide stock in the biomass of phytocenoses and 49.8–54.7 % of its total stock in terrestrial and aboveground biomass, 90Sr – 33.4–50.4 and 39.3–56.8 %, respectively. The radionuclide content in forest litter of oak forests is spatially extremely heterogeneous. The range of fluctuations of specific activity of 137Cs in them reached 19.4 times, 90Sr – 96 times, 137Cs stock – 30.5 times, 90Sr – 146 times. The radionuclide content in forest litter increased in the typological series Quercetum sublveto-fluvialis – Quercetum oxalidosum – Quercetum aegopodiosum – Quercetum graminoso-fluvialis. Individual values of 137Cs stock in individual forest types varied within 5.5–11.1 times, 90Sr – 2.7–69.5 times. 137Cs and 90Sr stocks in forest litter of oak forests are related to their specific activity in 20-cm soil layer, distance to the point of emission, growing conditions, productivity of stands; 137Cs stocks – to the thickness and biomass of forest litter; 90Sr stocks – to the share of deciduous species admixture in the composition of stands. Weather-climatic factors have a significant influence on radionuclide retention by forest litter.